Conventional and Conformal Radiotherapy with and without Beam Intensity Modulation in Patients with Stage II Hodgkin’s Lymphoma with Supradiaphragmal Lesions - YuN Vinogradova; EI Ivanova; AI Chumachenko; EV Smirnova; GI Andreev; AM Kalesnik; NA Vorob’ev; NV Il’in (Клиническая онкогематология)
Aim. To increase the efficacy of chemo-radiotherapy in patients with stage II Hodgkin’s lymphoma (HL) with supradiaphragmal lesions by different fractionation (conventional fractionation [CF] and multi-fractionation [MF]) and various radiation volume (mantle radiotherapy, involved field radiotherapy [IFRT] or involved site radiotherapy [ISRT]).